2005
DOI: 10.1093/jac/dki365
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of resistance in multidrug-resistant serovars of Salmonella enterica isolated from foods in Germany

Abstract: This study confirms the role of foods of animal and other origin as a reservoir of multidrug-resistant Salmonella and underlines the need for continuing surveillance of food-borne zoonotic bacterial pathogens along the food chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
55
2
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 41 publications
11
55
2
9
Order By: Relevance
“…As described previously (10,16,17,26), a strong association of class 1 integrons (1,000, 1,000 and 1,200, and 1,600 bp) with identified resistance to specific antibiotics was demonstrated and attributed in part to the existence of resistance genes (aadA for streptomycin and spectinomycin, aadB for gentamicin and kanamycin, and ␤-lactamase for ampicillin) within these integrons. The gene sequencing and associated antibiotic resistance profiles of each integron group suggest that the 1,600-bp integron in part shares a common ancestor with the 1,000-bp integron plus additional genetic material containing the aadB gene.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…As described previously (10,16,17,26), a strong association of class 1 integrons (1,000, 1,000 and 1,200, and 1,600 bp) with identified resistance to specific antibiotics was demonstrated and attributed in part to the existence of resistance genes (aadA for streptomycin and spectinomycin, aadB for gentamicin and kanamycin, and ␤-lactamase for ampicillin) within these integrons. The gene sequencing and associated antibiotic resistance profiles of each integron group suggest that the 1,600-bp integron in part shares a common ancestor with the 1,000-bp integron plus additional genetic material containing the aadB gene.…”
Section: Discussionsupporting
confidence: 69%
“…The tetB gene, conferring resistance to tetracycline, is carried on the Tn10 transposon (14). Sulfisoxazole resistance carried by the sulI gene is part of the 3Ј conserved sequence (17), and chloramphenicol resistance, imparted by the S. enterica serovar Typhimurium flo gene, was not carried on integrons (1). The source of resistance to spectinomycin by isolates not carrying integrons is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common resistance was to streptomycin (75%), ampicillin (59.4%), tetracycline (46.9%), and spectinomycin (40.6%), which is in agreement with the present study. Miko et al [32] determined antimicrobial resistance of Salmonella serovars isolated from German foodstuff; they showed that the most prevalent resistance among the multidrug-resistant Salmonella serovars isolated from foods were to streptomycin (94%), sulfamethoxazole (92%), tetracycline (81%), ampicillin (73%), spectinomycin (72%), chloramphenicol (48%), and trimethoprim (27%). The result regarding nitrofurantoin with 50% resistance is in agreement with that of Tassios et al [33] in Brazil, who reported 57.82% resistance among Salmonella isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Quinolones and fluoroquinolones are broad-spectrum antimicrobial agents that target DNA gyrase (gyrA and gyrB) and topoisomerase IV genes (parE and parC), and the resulting drug-enzyme-DNA complex inhibits DNA synthesis [13]. Mobile genetic elements such as plasmids, transposons, and the more recently explored integrons, which are able to disseminate antibiotic resistance genes by horizontal or vertical transfer, have played an important role in the evolution and dissemination of MDR in Gram-negative bacteria [20,21]. Further investigations are required to identify the genetic nature of antibiotic resistance of the 13 S. Infantis strains.…”
Section: Resultsmentioning
confidence: 99%